An Integrative Investigation of Sources, Fate, and Transport of Bacteria in Milwaukee Coastal Beaches - (:unkn) unknown (My University, 2013)
Beach water quality criteria are determined by the Environmental Protection Agency (EPA) and water quality advisories or closings are issued based on fecal indicator bacteria (FIB) at the beaches. Understanding of sources, fate and transport of FIB at a beach environment is of economic and social interest for public users, beach managers, policy makers and scientists. This is a complex problem and it is a multidisciplinary issue by nature. Scientists have generally taken a reductionist approach to tackle complex environmental issues. However, as alluded by Gallagher and Appenzeller (1999) and adopted by Boehm (2000), many complex systems are best interpreted using an "integrative agenda". Sources and transport of bacteria at a beach environment has been studied by Boehm (2012) in this context. Results from such study indicate that large scale feature is best interpreted with information about small-scale interactions. In this dissertation, I examined the sources of fecal indicator bacteria (FIB) in ten Lake Michigan beaches. In depth studies were performed at one study site (Bradford Beach) to investigate possible sources of FIB, including groundwater-lake water interactions and runoff infiltrating through the sand. The impact of hydrological and geophysical factors that are associated with formation of standing water were also investigated, including the potential of FIB reservoirs in the sand matrix to serve as a sink and source of bacteria at the beach environment. In order to better understand bacterial association with particles at a large scale, I examined the small scale interactions between bacteria and particles by developing a new non-invasive optical technique and applying the technique to assess attachment of bacteria to sand particles in a sheared fluid simulating condition found in the surf zone. Finally, I used knowledge obtained from the understanding of small scale interactions to interpret results acquired from a statistical model and time series applied to large scale features at Bradford Beach and Atwater Beach. This work is relevant to the study of sources and transport of bacteria not only in large lakes, but in rivers and oceans. The results also extend to the investigation of other microbial pollutants and their association with particles in a water body and the potential to track the transport of these pollutants in sediments, air and water. References: Boehm, A. (2000). "An integrative investigation of particle distributions in natural waters." Department of Chemical and Biochemical Engineering and Materials Science. Irvine, University of California, Irvine: 194. Gallagher, R and T. Appenzeller (1999). "Beyond reductionism." Science 284:79. Russell, T. L., K. M. Yamahara and A. B. Boehm (2012). "Mobilization and transport of naturally occurring enterococci in beach sands subject to transient infiltration of seawater." Environmental Science and Technology 46:5988-5996.
Keywords: Fecal Indicator Bacteria; Lake Michigan Beaches; Sediment Particles